How to improve agricultural value-added in the MENA region? Implementation of Diamond Porter's theory in agriculture - Nugroho, Agus Dwi; Istvan, Feher; Fekete-Farkas, Maria; Lakner, Zoltan (Frontiers in Sustainable Food Systems, 2022)
The global economy in recent decades has experienced frequent shocks. Many regions must improve their competitiveness and value-added to deal with this. One of them is in the Middle East and North Africa (MENA), where a rise in agricultural value-added (AVA) can produce more jobs than in other sectors. It is necessary to consider increasing AVA in the MENA region. Hence, the aim of this study is identifying the determinant factors of AVA in the MENA region. We employed 13 countries in the MENA region as samples in this study. The study's data spans 45 years, from 1975 to 2019. Static panel data regression analysis was employed in this study. AVA can growth by increasing the irrigated land, credit, and human capital. Meanwhile, growing inflation and economic globalization will reduce AVA. Therefore, we recommend that countries in the MENA region have to increase irrigation infrastructure, expand agricultural credit availability, encourage farmers to get a good education, improve research and development, control inflation, and find the best way to implement economic globalization.